2005
DOI: 10.1021/jp053563b
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Iridium Nanoparticles Using Density Functional Theory Calculations

Abstract: The energetics and the electronic and magnetic properties of iridium nanoparticles in the range of 2-64 atoms were investigated using density functional theory calculations. A variety of different geometric configurations were studied, including planar, three-dimensional, nanowire, and single-walled nanotube. The binding energy per atom increases with size and dimensionality from 2.53 eV/atom for the iridium dimer to 6.09 eV/atom for the 64-atom cluster. The most stable geometry is planar until four atoms are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

28
103
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 92 publications
(132 citation statements)
references
References 46 publications
28
103
1
Order By: Relevance
“…The Ir 4 clusters show average and local magnetic moment of 2.13l B /atom, in agreement with experimental values (2.04l B /atom) reported for the tetrahedral Ir 4 cluster (Stevanovic et al 2012). Pawluk et al (2005) also reported 2l B /atom for the square isomer, however, they have obtained zero magnetic moment for the tetrahedral structure. For the tetramers also, the presence of Fe in the neighborhood enhances the Ir moments and the average magnetic moment increases with Fe concentration.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…The Ir 4 clusters show average and local magnetic moment of 2.13l B /atom, in agreement with experimental values (2.04l B /atom) reported for the tetrahedral Ir 4 cluster (Stevanovic et al 2012). Pawluk et al (2005) also reported 2l B /atom for the square isomer, however, they have obtained zero magnetic moment for the tetrahedral structure. For the tetramers also, the presence of Fe in the neighborhood enhances the Ir moments and the average magnetic moment increases with Fe concentration.…”
Section: Resultssupporting
confidence: 89%
“…The predicted stable geometries in theoretical studies include tetrahedral (Feng et al 1997), a butterfly structure (Bussai et al 2005), rhombus (Pawluk et al 2005), and square (Stevanovic et al 2012) whereas experiments has showed tetrahedral as the most stable structure having a bond length of 2.71 Å (Deutsch et al 1997). We have seen that the tetrahedral structure is the most stable structure in agreement with this experimental result and theoretical study which obtained tetrahedron having bond length of 2.79 Å (Feng et al 1997).…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations